Restless Legs Syndrome: From Pathophysiology to Clinical Diagnosis and Management - Guo, Shiyi; Huang, Jinsha; Jiang, Haiyang; Han, Chao; Li, Jie; Xu, Xiaoyun; Zhang, Guoxin; Lin, Zhicheng; Xiong, Nian; Wang, Tao (Frontiers in Aging Neuroscience, 2017)
Restless legs syndrome (RLS), a common neurological sensorimotor disorder in western countries, has gained more and more attention in Asian countries. The prevalence of RLS is higher in older people and females. RLS is most commonly related to iron deficiency, pregnancy and uremia. The RLS symptoms show a significant circadian rhythm and a close relationship to periodic limb movements (PLM) in clinical observations, while the pathophysiological pathways are still unknown. The diagnostic criteria have been revised in 2012 to improve the validity of RLS diagnosis. Recent studies have suggested an important role of iron decrease of brain in RLS pathophysiology. Dopaminergic (DA) system dysfunction in A11 cell groups has been recognized long ago from clinical treatment and autopsy. Nowadays it is believed that iron dysfunction can affect DA system from different pathways and opioids have a protective effect on DA system. Several susceptible single nucleotide polymorphisms (SNPs) such as BTBD9 and MEIS1, which are thought to be involved in embryonic neuronal development, have been reported to be associated with RLS. Several pharmacological and non-pharmacological treatment are discussed in this review. First-line treatments of RLS include DA agents and α2δ agonists. Augmentation is very common in long-term treatment of RLS which makes prevention and management of augmentation very important for RLS patients. A combination of different types of medication is effective in preventing and treating augmentation. The knowledge on RLS is still limited, the pathophysiology and better management of RLS remain to be discovered.